PiViewer: An open‐source tool for automated detection and display of π–π interactions. (13th June 2018) - Liu, Ying; Ao, Xiang; Wang, Qiong; Wang, Jianxun; Ge, Hu
Abstract : π – π interactions are common and important noncovalent interactions that contribute to biochemical molecular interactions, but the tools for the convenient 3D visualization of π – π interactions are lacking. We have developed an open‐source and easy‐to‐use tool for the automated identification and display of π – π stacking in 3D. It can percept the aromaticity of rings from any selected ligand and the surrounding residues, calculate the distances and dihedral angles between each pair of aromatic ring planes, as well as can highlight the various configurations of π – π interactions in 3D: the sandwich configuration, the T‐shaped configuration, and the parallel‐displaced configuration. In addition, the users can easily adjust or set their own criteria for π – π stacking. Abstract : We have developed an open‐source and easy‐to‐use tool for the automated identification and display of π – π stacking in 3D. It can percept the aromaticity of rings from any selected ligand and the surrounding residues, calculate the distances and dihedral angles between each pair of aromatic ring planes, as well as can highlight the various configurations of π – π interactions in 3D.